DESENVOLVIMENTO DE HETEROESTRUTURA À BASE DE HIDROXIAPATITA E MAGADIÍTA PARA REMOÇÃO DE CIPROFLOXACINA EM MEIO AQUOSO - MARTINS, Jaynne dos Santos (2025)
The growing concern about environmental pollution has driven the investigation of emerging contaminants, such as antibiotics, due to their adverse impacts on aquatic ecosystems. In this context, heterogeneous photocatalysis has emerged as a promising approach for the degradation of these pollutants. Based on this, the present work proposes the development of an efficient photocatalyst by combining silver-doped hydroxyapatite (Hap-Ag) supported on magadiite (Mag), aiming at its application in remediation processes. The materials were synthesized using a hydrothermal method (for Magadiite) and in situ precipitation (for Hap derivatives), and characterized by X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM) with energy-dispersive X-ray spectroscopy (EDS), nitrogen adsorption-desorption isotherms (BET), and diffuse reflectance spectroscopy (DRS), to determine the most efficient composition. The photocatalytic activity was evaluated for the degradation of the antibiotic ciprofloxacin, with optimization of the reaction parameters. Under UV irradiation, using 50 mL of solution (10 ppm) at pH 4 and 30 mg of catalyst, the heterostructure Hap-Ag1/Mag5 achieved 100% removal within 90 minutes. The material also exhibited good stability, maintaining over 50% efficiency after five reuse cycles. The lowest Non-purgeable organic carbon value observed for this sample indicates a more efficient contaminant mineralization. In the electrochemical tests, the Nyquist plot showed a smaller semicircle radius for the Hap-Ag1/Mag5 sample, suggesting lower charge transfer resistance, possibly associated with better silver dispersion and the formation of a more efficient conductive network. The transient photocurrent response showed the highest current peaks under illumination, indicating more effective separation of electron-hole pairs. Finally, radical scavenger tests indicated that photoexcited holes (h⁺) are the main reactive species involved in the degradation mechanism. These results highlight the potential of the developed heterostructure for applications in the treatment of water contaminated by pharmaceuticals.